Effect of mango juice on frozen yoghurt Quality - Makawi, Manal Mirghani; Razig, Kamal Awad Abdel (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The effect of different amounts of mango juice (0.0%, 25%, 50% and 75% vol/w) on the quality of frozen yoghurt was investigated. All samples ingredients (yoghurt, low fat, sugar cream, gum Arabic, sugars) were mixed with the indicated amount of juice and then transferred to an ice cream machine so that the final product could be packed into plastic cups and stored in a deep freezer at -18 0 C for 45 days. Samples were analyzed on day 0, 15, 30 and 45 of the storage period. Physicochemical analyses showed that, the 75% mango juice had the highest content of total solids (28.80%), protein (9.60%), fat (14.60%), ash (2.50%) and fiber (1.20g/100g). The pH of all samples decreased, while the titratable acidity increased during storage. Organoleptic characteristics were significantly affected (P≤0.05) by the presence of mango juice. The best appearance (4.7%), texture (4.6%), flavour (4.8%) and over all acceptability (4.7%) were recorded in containing 25% mango juice. The storage period also significantly (p≤0.05) affected the quality of the frozen yoghurt with the best scores obtained at the beginning of the storage period.